TEACHING ENGLISH AS A FOREIGN LANGUAGE IN THE CLASS: SOCIOLINGUISTICS’ VIEW - Roda’i, Muhammad (The Ellite of Unira, 2024)
Language is a means of communication among individuals and it also brings them into relationships with their culture. Even the English language as foreign language involving culture. The result all languages are equally complex because every language is part of the culture that produces it and it is adequate for the needs of the people who use it. Any language, therefore, is as good as any others because it serves the purposes of the particular culture. Seeing this, this paper aims at describing about the important of culture in teaching and learning English in the foreign language classroom. It is hoped that the students realize to have socio-cultural competence with the teacher’s help, with the hope, he wishes, not only to teach linguistics (grammar/ structure, pronunciation, etc.) but also sociolinguistics (social and culture). It is very essential to avoid misunderstanding, justification or ‘shock culture’ so that they can communicate with any English men well.